2022
DOI: 10.1080/14786419.2022.2118742
|View full text |Cite
|
Sign up to set email alerts
|

New acylphloroglucinols from a crude acetone extract of Eucalyptus camaldulensis Dehnh. leaf

Abstract: Acylphloroglucinols are well-known Eucalyptus secondary metabolites which exhibit a variety of structures and bioactivities. The investigation of a crude acetone extract of Eucalyptus camaldulensis leaves led to the isolation of two new acylphloroglucinols, eucalypcamals O and P (1 and 2) together with seven phloroglucinols (3-9), and a benzene derivative (10). Their chemical structures were elucidated by 1D and 2D nuclear magnetic resonance (NMR) spectroscopy and mass spectroscopy. The absolute configurations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…aureus (MSSA and MRSA) among the seven compounds tested in this study. It is also almost twice as active as eucalrobusone F, the most active compound previously reported from E. camaldulensis . , Furthermore, 2 is twice as active compared to its regioisomer 3 suggesting that the position of formyl and/or isovaleryl substituents in the dihydropyran fused phloroglucinol affects activity. The regiochemistry of the acyl group in the potently active compound rhodomyrtone vs its acyl regioisomer rhodomyrtosone B points to the importance of acyl regiochemistry for antibacterial activity in acylphloroglucinols .…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…aureus (MSSA and MRSA) among the seven compounds tested in this study. It is also almost twice as active as eucalrobusone F, the most active compound previously reported from E. camaldulensis . , Furthermore, 2 is twice as active compared to its regioisomer 3 suggesting that the position of formyl and/or isovaleryl substituents in the dihydropyran fused phloroglucinol affects activity. The regiochemistry of the acyl group in the potently active compound rhodomyrtone vs its acyl regioisomer rhodomyrtosone B points to the importance of acyl regiochemistry for antibacterial activity in acylphloroglucinols .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A small number of FPCs have previously been tested at independent laboratories and shown to possess comparable antibacterial activities (for example macrocarpals A and C/G). However, a recent study has reported antibacterial activities as MIC 50 (in μg/mL) and this resulted in macrocarpals A and B and eucalyptal A and the positive control caiprofloxacin being reported with activities 10 to 100-fold more potent than the those reported using the more generally accepted measure of MIC. ,,, Consequently, the activities of all compounds reported by Liu et al 2022 have been shifted by an order of magnitude to make for more meaningful comparisons . Furthermore, we have recently developed a tool to check the validity of NMR assignments for FPCs and the structures of the four new compounds eurobusones A–D, reported by Liu et al 2022 are questionable since their NMR data poorly matches with that predicted for their substructure classes .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations